2019
DOI: 10.1111/vop.12658
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of slit lamps in veterinary ophthalmology

Abstract: Purpose: Healthcare-associated infection (HAI) is a well-known problem in human medicine. The contamination of medical devices with pathogenic organisms is less studied in veterinary medicine. The purpose of this multicenter study was to evaluate the bacterial contamination of slit lamps throughout Europe and part of the United States. The efficacy of standard cleaning was additionally investigated. Methods: Samples from adjustment wheels of slit lamps were taken by different veterinary ophthalmologists and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…Contamination of ophthalmic equipment ranged from 41.7% (5/12) to 43.5% (10/23) in the retrospective and prospective studies, respectively, with an overall prevalence of 42.9% (15/35). These findings are fairly similar to a recent report by Casola and colleagues, who detected pathogenic bacteria in 58.6% of handheld slit lamps used in a veterinary practice (8). It would be interesting to determine whether contamination is more common in select ophthalmic equipment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Contamination of ophthalmic equipment ranged from 41.7% (5/12) to 43.5% (10/23) in the retrospective and prospective studies, respectively, with an overall prevalence of 42.9% (15/35). These findings are fairly similar to a recent report by Casola and colleagues, who detected pathogenic bacteria in 58.6% of handheld slit lamps used in a veterinary practice (8). It would be interesting to determine whether contamination is more common in select ophthalmic equipment.…”
Section: Discussionsupporting
confidence: 89%
“…Undoubtedly, proper cleaning protocols can reduce bacterial levels in examination rooms and minimize the risk for nosocomial infections (24,25), as exemplified by a significant decrease in bacterial contamination of handheld slit lamps from 58.6 to 13.8% following disinfection (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary infectious keratitis in dogs is uncommon ( 45 ). Corneal infection is usually enhanced by disruption of the defense mechanism of the ocular surface, which includes the structural integrity and blinking action of the eyelids, and the intact epithelium of the conjunctiva and cornea ( 46 ). Microtrauma is the predominant factor contributing to the development of keratitis; other causes are tear film disturbances, disorders of the immune system (immunodeficiencies and autoimmune diseases), and corneal surgical interventions ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a survey about the breeding information in 2,168 brachycephalic dogs has been conducted, and the results showed that there were 15.4% of dogs had ever suffered from a bacterial corneal ulcer, and nearly one-quarter breed (22.9%) was the Pug (24). The common causes of corneal ulcers in dogs included trauma, foreign bodies, infection, and inadequate lacrimal secretion or others (25,26). A survey from 2015 to 2016 in Thailand has indicated that 32 ulcers samples, 26 (81.3%) samples yielded culturable microorganisms with 24 bacterial isolates, and 7 fungal isolates (27).…”
Section: Discussionmentioning
confidence: 99%